The Jews in Hollywood: Altering Image through Religious Movies - Witriani, Witriani (Soegijapranata Catholic University, 2019)
This article discusses the altering image of American Jews in Hollywood movies. Coming to America during the great migration, mostly from Eastern Europe, this Azkenazic Jews then contributed to the building and transformation of the Hollywood movies as a world icon. Though quite dominant, Jews are quite careful in this industry. Anti-Semitism, the World War and the Great Depression are some of the things that make Jews uncomfortable about being in the spotlight or talking about their identity among the Christian audience of the movies. However, the condition changed after the Second World War and the civil rights movement in the 1960s. Jews and Judaism later appeared in various representations, which does not only change their image in Hollywood, but also the acceptance of American society broadly. Focusing on the movie, Ben Hur: A Tale of the Christ (1959) as the object of research, the study explores how Jewish people represent themselves through films produced, including the negotiations and changes made as part of the American Jews. Using the theory of Stuart Hall’s Politics of Representation and Critical Discourse Analysis from Fairclough and Leuween as an approach, this work focuses on the analysis of text and images as a sign that represents the Jews and Judaism in the movie. Related to movie as a media construction, the filmmakers are able to reconstruct Jews in different image. Through the movie, the represented Jews are found to have conveyed various messages to the audience about their cultural and religious identity.